Traditional Medicinal Plants Used as Anti-cancer in the Philippines: A Systematic Ethnobotanical Review - Cabanlit, Kathleen; Torres, Mark Anthony; Demayo, Cesar (Ethnobotany Research and Applications, 2024)
Background: As an archipelagic tropical country, the Philippines hosts abundant and diverse medicinal plants that have long been utilized as herbal remedies for diseases like cancer by over 112 ethnolinguistic groups, along with the locals, across its islands. With this diversity, a comprehensive identification of common anticancer herbal remedies is deemed important to serve as an exhaustive reference list for validating the efficacy of traditionally used medicinal plants against cancer. However, existing ethnobotanical records are limited to studies that conduct general ethnobotanical documentation which are not specified for anticancer use only. Hence, this review compiled previous studies on medicinal plants used as anticancer by locals and ethnic groups in the Philippines. Methods: Studies with information on medicinal plants used for anticancer were obtained from ScienceDirect, PubMed, DOAJ, Google Scholar, and MSU-IIT DBS. Titles, abstracts, and articles were reviewed independently by three reviewers, and the quality of included studies was then evaluated using a quality assessment tool specific to ethnobotanical studies. The PRISMA design was used to carry out this review from inception to April 25, 2024. Results: The qualitative synthesis included 71 new studies mostly conducted in Mindanao, followed by Luzon and Visayas, respectively. A total of 68 families, 145 genera, and 390 plant species were documented, of which the most commonly mentioned were the families Zingiberaceae, Annonaceae, and Apocynaceae. Meanwhile, the most frequently cited genera were Annona, followed by Curcuma and Ficus. Plant parts commonly used for anticancer preparations were leaves, roots, and fruits, respectively, with decoction being the predominant mode of preparation. Annona muricata emerged as the most commonly mentioned plant species, followed by Curcuma longa and Catharanthus roseus. Conclusions: This review showed that the widespread and sustained utilization of herbal plants with anticancer properties across the Philippines is pivotal in cancer healthcare in the country, reflecting the deeply-rooted traditional knowledge and practices within local communities. Moreover, many similarities in ethnobotanical practice were observed across the claimants, hence showing the shared knowledge of traditional medicinal practices among different Filipino communities. Keywords: Philippines, medicinal plants, ethnobotany, anticancer, herbal remedies, herbal preparations, traditional knowledge, indigenous